Angiographically proven hypothenar hammer syndrome in a school teacher - A. R., Ezamin; S., Suppiah; H., Abu Hassan; S., Mohd Saini; B., Norafida; S., Ab Hamid; S. N., Abd Rashid; R., Mahmud (Community Health Society Malaysia, 2016)
Hypothenar hammer syndrome (HSS) is a rare condition caused by thrombosis of the superficial palmar branch of the ulnar artery, known to occur in people who use the hypothenar or medial aspect of their hands literally as a hammer in a routine or habitual manner, leading to ischaemia of the hands. Certain occupational and recreational activities have been reported to predispose to this trauma-induced condition, however, there are no reports documenting this syndrome in a school teacher. Most studies have also been diagnosed on clinical and ultrasound imaging grounds. However, conventional upper limb angiography is considered the gold standard as of late, and it has been able to diagnose this condition more frequently, after exclusion of other risk factors such as connective tissue disease and congenital vascular malformations. We report a case of a teacher who presented with pain and weakness of his dominant hand, which has been angiographically proven to be due to ulnar artery occlusion at the palmar arch. This article can help explain a potentially debilitating condition that has never been reported before in a teacher, thus highlighting possible behavioural related occupational hazards that can be avoided.